2007
DOI: 10.1590/s1415-47572007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Satellite DNA sites in four species of the genus Astyanax (Teleostei, Characiformes)

Abstract: Cytogenetic data about satellite DNA distribution in four Astyanax species (Characidae) from the Paraitinga river, Paraíba do Sul river basin, Brazil, are presented. In order to characterize the constitutive heterochromatin, C-banding, chromomycin A 3 and DAPI fluorescence staining, as well as fluorescence in situ hybridization (FISH) with the satellite DNA As-51 probe were performed. A. scabripinnis and A. parahybae presented 2n = 50 and 2n = 48 chromosomes, respectively. The heterochromatin was located in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
(24 reference statements)
4
10
0
Order By: Relevance
“…costal drainages, upper Tietê River) present few As51 DNA sites, while individuals found in inland basins (e.g. Paranapanema and Mogi-Guaçu river) may present several sites [Abel et al, 2006;Kavalco et al, 2007Kavalco et al, , 2011Kavalco et al, , 2013Pazza et al, 2008]. Although we have not mapped the As51 DNA in the present study, the heterochromatin distribution patterns found are very similar to those presented in Kavalco et al [2013] in specimens collected at Salesópolis, SP (upper Tietê River), confirming the proposed scenario.…”
Section: Discussionsupporting
confidence: 83%
“…costal drainages, upper Tietê River) present few As51 DNA sites, while individuals found in inland basins (e.g. Paranapanema and Mogi-Guaçu river) may present several sites [Abel et al, 2006;Kavalco et al, 2007Kavalco et al, , 2011Kavalco et al, , 2013Pazza et al, 2008]. Although we have not mapped the As51 DNA in the present study, the heterochromatin distribution patterns found are very similar to those presented in Kavalco et al [2013] in specimens collected at Salesópolis, SP (upper Tietê River), confirming the proposed scenario.…”
Section: Discussionsupporting
confidence: 83%
“…In relation to rDNA 5S, most of the species/populations already analyzed have the same following pattern: one site on the marker chromosome plus a pair of acrocentric chromosomes with a rDNA 5S site in the proximal region; this was also observed in the specimens analyzed in the present work ( Kavalco et al, 2004 , 2007 , 2009 , 2016 ; Pazza et al, 2006 ) and in the literature available for A. bockmanni , A. fasciatus , and A. parahybae ( Almeida-Toledo et al, 2002 ; Hashimoto et al, 2011 ; Silva et al, 2013 ; Daniel et al, 2015 ). Despite this relatively conserved pattern, there are two autapomorphies in the 5S rDNA phenotype in A. fasciatus .…”
Section: Discussionsupporting
confidence: 76%
“…These other species are less studied by cytogenetic methods, but until now, the chromosome characteristics seems to be shared ( Mendes et al, 2011 ; Coutinho-Sanches and Dergam, 2015 ), bringing new evidence supporting the group. Unfortunately, As51 repetitive DNA in these coastal distribution species has not been confirmed so far ( Kavalco et al, 2007 , 2009 ).…”
Section: Discussionmentioning
confidence: 98%
“…There are certain groups characterized by large amounts of heterochromatin at terminal position [21,26], that enable to determine cases of both inter-and intraindividual polymorphism [16,17]. On the other hand, these conspicuous blocks are absent in some other species [8,9,13,14,21], although all species share small C-bands at pericentromeric region and interspersed with NORs, similar to the pattern herein described for A. ribeirae (Fig. 2a).…”
Section: Discussionsupporting
confidence: 56%
“…2a). Data about the inter-specific homology of a satellite DNA isolated from A. scabripinnis carrying sequences similar to transposable elements [19] have shown that such DNA sequence was quite dispersed in some species, like in the A. scabripinnis and A. fasciatus groups [1,17,26], but is absent in coastal species, like A. giton, A. intermedius and A. hastatus [9,13].…”
Section: Discussionmentioning
confidence: 99%